Simultaneous thermal analysis on the dynamical oxygen-lean combustion behaviors of coal in a O2/N2/CO2 atmosphere. (June 2021) - Su, Hetao; Kang, Ning; Shi, Bobo; Ji, Huaijun; Li, Yunzhuo; Shi, Jingdong
Abstract: This study aims at study the dynamical oxygen-lean combustion behaviors of coal in a multi-gas concomitant atmosphere. Two coal samples from Bulianta and Yuwu collieries were collected for simultaneous thermal analysis in O2 /N2 (21 vol%/79 vol%) and O2 /N2 /CO2 (15 vol%/80 vol%/5 vol%) atmospheres. Based on the TG-DTG curves, five evolution stages were analyzed. A delay phenomenon occurred for coal lean-oxygen combustion in O2 /N2 /CO2, which was obvious at IV stage with a high staged temperature and a wide temperature range. Furthermore, the kinetic parameters were obtained after determining the most probable mechanism function, showing an increased apparent activation energy at III stage and a decreased one at IV stage in O2 /N2 /CO2 compared with in O2 /N2, which indicated that the low heat conduction coefficient of CO2 played a dominant role on these changes. The study also showed the relationship between the thermal formation rate and reaction rate constant. Highlights: Dynamical oxygen-lean combustion of coal in a multi-gas concomitant atmosphere. Delays at five evolution stages of coal combustion in O2/N2/CO2. Determination of the most probable mechanism functions at different stages. A dominant role of Low heat conduction coefficient of CO2 on kinetics changes. Relationship between the thermal formation rate and reaction rate constant.